Sources and Sociology Concerns of Financing the Innovation Activities in Russia - Sergeevna, Budovich Lidia; Yurievna, Nikolaeva Olga (International Journal of Criminology and Sociology, 2021)
The innovation abilities of an enterprise and the feasibility of an innovative project always depend on financing. We can say that the main issue is the assessment of funds required for the implementation of an innovation and the analysis of their possible sources. In this paper, different mechanisms of financing and allocation of financial resources and their impact on innovative performance were examined. In general, financing sources of the institutes in different countries have adopted different mechanisms to provide and allocate resources from the range of public funding to private financing. But the amount varies from country to country so that in European institutions most government funding and the United States, private financing is the predominant form of financing. Some governments subsidize the supply side (higher education institutions), some on the demand side (customers), and some on both sides of the higher education services market. In general, negotiation-based and formula-based allocation, personnel-based allocation, student-based allocation, per capita cost, priority-based, and performance-based allocation are among the mechanisms used in this regard. The results of this article showed that the mechanisms of allocating and allocating resources in higher education play the role of policy-making and guiding the behavior of actors and can affect the performance of universities and institutions of higher education at the macro and micro level (individual). In the area of funding, graduates should contribute to the financing of universities, and in the area of allocation, performance-based allocation mechanisms should be used to achieve greater efficiency, accessibility, and equity.